Workforce Diversity And Employee Performance: Evidence From Selected Fast-Food Centres In Osun State, Nigeria - Ayodeji Muyideen Awolaja; Olumayowa Kabir Otulana; Olatunde Misbaudeen Osuolale; Alirat Molade Ibrahim Ahmed; Sunday Adeniyi Olasehinde (Universitas Indonesia Membangun (Inaba), 2025)
Workforce diversity has emerged as a critical element in today’s organizational landscape, particularly in service-driven industries where interactions, collaboration, and innovation are central to performance. However, managing diversity effectively remains a significant challenge, especially in developing economies such as Nigeria. This study investigates the influence of workforce diversity on employee performance in selected fast-food centres in Osun State. Adopting a quantitative research approach and a descriptive-causal comparative design, primary data were gathered through 150 structured questionnaires administered to employees, with 135 valid responses analyzed using descriptive statistics and regression analysis. Findings revealed that workforce diversity significantly predicts employee performance (R = 0.742, R² = 0.550, p < 0.05), which confirmed that diversity accounted for 55% of performance variation. Specifically, age, gender, and ethnic diversity had strong positive effects, while religious diversity showed a modest but positive influence. The findings underscore the importance of inclusive workplace practices in enhancing collaboration, efficiency, and customer satisfaction. The study recommends that fast-food organizations institutionalize diversity management policies, implement diversity awareness and sensitivity training, and adopt equitable recruitment and promotion strategies to maximize performance outcomes.